Vectorial mechanism of nonlinearity enhancement in rubidium vapor - Korneev, Nikolai; Gutiérrez Parra, Chrystian (Acta Universitaria, 2013)
We report the calculations of vectorial nonlinear properties of rubidium vapor for 87Rb D2 transition at moderate intensities. Different from Kerr nonlinearity, optimal intensity exists here, which depends on beam geometry. For intensities close to the optimal, the vectorial mechanism is much more efficient than a scalar one.